Genotypes Performance, Characterization and Genetic Variability Studies of Sweet Pepper Accessions for Different Traits - Saha, Swati; Chandrashekar, K.; Singh Kushwah, Sujan; Mahapatro, G. K. (International Journal of Bio-resource and Stress Management, 2023)
The study was conducted during two consecutive years 2018–2019 and 2019–2020 at IARI, Regional Station, Pune, Maharashtra, India to evaluate for genetic variability, heritability and genetic advance of nineteen genotypes. Our objective was to select the promising genotypes under open condition with better horticultural attributes under Western Maharashtra plain zone. Based on average of two years data, total yield ranged from 1.79-4.22 t ha-1 and maximum observed in Orobelle Yellow. TSS ranged from 6.35–9.66°Brix, maximum in KTC-153 while Vitamin C content varied between 129.99–175.57 mg 100 g-1 FW maximum in ATS-89. Phenotypic coefficient of variation (PCV) was greater than genotypic coefficient of variation (GCV) for all traits. However, GCV values were near to PCV values for most of the characters indicating high contribution of genotypic effect for phenotypic expression. High heritability coupled with high genetic advance (Mean %) was obtained for plant height, number of fruits plant-1, yield plant-1, yield ha-1, fruit length, fruit diameter, fruit cavity, fruit weight, number of seeds per fruit, and hundred seed weight, reflecting the presence of additive gene effects for the expression of these traits. Genotypes NS-281, KTP-141, SH-SP-4-1, SH-SPH-603, ATS-89, ATS-86, KTC-153, ATS-86 were found promising in one or the other characters like number of fruits plant-1, yield plant-1, yield (t ha-1), Vitamin C content, TSS. These lines can be used as pre-breeding material for hybridization programme.